#TITLE_ALTERNATIVE# - MUNANDAR (NIM 13602024), HARRY
The goal of this final project is to determine aircraft price and particular factor which can influence the price of WISE 8. Aircraft price can be obtained by estimation and calculation of aircraft cost elements. Having the price determined, the break event point is estimated with certain rate and quantity aircraft production. The cost estimation is put forward by using three methods: engineering estimation, analogy estimation, and parametric estimation. Parametric estimation is based on three references: Roskam, Raymer, and Nicolai. The references use similar empiric equations taken from the statistical data of aircraft manufactures, while the engineering estimation is analyzed by calculating the current engineering and prototype costs taken from the manufacturer of WISE 8. The result shows that the parametric estimation using Roskam and Raymer references gives overlimit WISE 8 price, but at the same getting closer to a single engine piston aircraft. In the result of engineering method, some elements of RDTE cost are unknown, so it is estimated. The engineering estimation shows that the price of WISE 8 in the range of US$ 320,883 to US$ 447,551, with the assumption of monthly production rate of 2 aircraft and RDTE cost is 30% higher than the preliminary estimation. Assuming that aircraft price per unit is US$ 382,229, the break even point of WISE 8 production can be achieved with 76 units aircraft in 3,2 years